THE USE OF MIMIND APP TO SUPPORT WRITING PERFORMANCE OF SECONDARY STUDENTS - Titi Lestari; Hasti Robiasih; Dinar Martia Azizah; Aqidah Danar Pambudi (Wiralodra English Journal, 2022)
The present study explores how Mimind app is implemented and what strengths and challenges this app brings to the writing class of the seventh-grade students of a secondary school in Kroya. This is an Action Research involving 16 seventh grade students. Documentation, observations, and interviews were used to gain the necessary data. The collected data were analyzed using qualitative analysis model from Miles, Huberman, and Saldana (2014). The results indicate that: (1) The implementation of Mimind App in teaching learning activities was executed through the five stages of Scientific Approach and there were some activities such as giving picture, giving model text, giving individual work, group work, completing and developing a mind map, and creating a descriptive text. (2) Several strengths of using Mimind App as an online learning medium are: (a) an increase in motivation through the level of participation and activeness of students in online learning process, (b) the creation of an interesting and fun learning atmosphere for students, (c) and an increase in students writing performance, i.e., students’ writing ability. However, challenges deal with sufficient time management to explore the richly-provided features of the application.